2019
DOI: 10.1038/s41598-018-36690-9
|View full text |Cite
|
Sign up to set email alerts
|

A 14-day repeat dose oral gavage range-finding study of a first-in-class CDI investigational antibiotic, in rats

Abstract: Drug resistant bacteria are winning the fight over antibiotics with some bacteria not responding to any antibiotics, threatening modern medicine as we know it. The development of new, effective and safe antibiotics is critical for addressing this issue. Ramizol, a first-in-class styrylbenzene based antibiotic, is an investigational drug indicated for Clostridium difficile infections (CDI). The objective of this range-finding study was to evaluate the potential general toxicity (based on toxicological endpoints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Short-term acute toxicity study: A time-line describing this protocol based on Sibley et al 23 is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Short-term acute toxicity study: A time-line describing this protocol based on Sibley et al 23 is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…70 A 14-day study was conducted in rats to determine possible toxicity from ramizol administered via oral gavage at repeat dosing that ranged from 50 mg/ kg, 500 mg/kg and 1500 mg/kg. 71 It was observed that high doses of ramizol at 1500 mg/kg/day were well tolerated. Phase I studies will be required to assess the safety of ramizol in healthy volunteers.…”
Section: Ramizolmentioning
confidence: 99%
“…It is also worth noting that several stilbene-based engineered drugs have been approved by the U.S. Food and Drug Administration agency (FDA) and the European Medicines Agency (EMA) and are effectively in use for estrogen-receptor modulating therapies such as raloxifene (osteoporosis in women), toremifene and tamoxifen (both in use for hormone receptor-positive breast cancer) [ 117 ]. Another stilbene derivate, Ramizol, is currently under preclinical investigation for the treatment of Clostridioides difficile infections [ 118 , 119 ].…”
Section: Polyphenols and Tanninsmentioning
confidence: 99%